2017
DOI: 10.7554/elife.23717
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric origins of ochrophytes and haptophytes revealed through an ancient plastid proteome

Abstract: Plastids are supported by a wide range of proteins encoded within the nucleus and imported from the cytoplasm. These plastid-targeted proteins may originate from the endosymbiont, the host, or other sources entirely. Here, we identify and characterise 770 plastid-targeted proteins that are conserved across the ochrophytes, a major group of algae including diatoms, pelagophytes and kelps, that possess plastids derived from red algae. We show that the ancestral ochrophyte plastid proteome was an evolutionary chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
221
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(229 citation statements)
references
References 150 publications
8
221
0
Order By: Relevance
“…Similarly, recent estimates have suggested that c . 25% of nucleus‐encoded plastid‐targeted proteins in the ancestor of ochrophytes (photosynthetic stramenopiles) have derived from green algae (Dorrell et al ., ). This apparent massive genetic mosaicism may be explained either as the result of a high frequency of eukaryote‐to‐eukaryote HGT or as the consequence of putative cryptic endosymbioses.…”
Section: Complex Plastidsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, recent estimates have suggested that c . 25% of nucleus‐encoded plastid‐targeted proteins in the ancestor of ochrophytes (photosynthetic stramenopiles) have derived from green algae (Dorrell et al ., ). This apparent massive genetic mosaicism may be explained either as the result of a high frequency of eukaryote‐to‐eukaryote HGT or as the consequence of putative cryptic endosymbioses.…”
Section: Complex Plastidsmentioning
confidence: 97%
“…For instance, despite diatoms containing plastids clearly derived from red algae, phylogenetic analysis of diatom nuclear genomes has suggested that > 1700 nucleus-encoded genes were apparently transferred from green algae (Moustafa et al, 2009). Similarly, recent estimates have suggested that c. 25% of nucleus-encoded plastid-targeted proteins in the ancestor of ochrophytes (photosynthetic stramenopiles) have derived from green algae (Dorrell et al, 2017). This apparent massive genetic mosaicism may be explained either as the result of a high frequency of eukaryote-to-eukaryote HGT or as the consequence of putative cryptic endosymbioses.…”
Section: Complex Plastidsmentioning
confidence: 99%
“…, Dorrell et al. , Leonard et al. ), the monophyly of the ochrophyte members of the stramenopiles strongly suggests that these groups radiated from a plastid‐bearing and photosynthetic ancestor, with any non‐photosynthetic members within them originating through secondary losses of photosynthesis (Ševčíková et al.…”
mentioning
confidence: 99%
“…The distinctive feature of the photosynthetic stramenopiles, in relation to other stramenopiles, is their possession of plastids acquired through secondary or higher endosymbiosis with a red alga or one of its subsequent evolutionary derivatives. Despite the existence of numerous non-photosynthetic organisms within stramenopiles (Patterson 1989, Sekiguchi et al 2002, Cavalier-Smith and Chao 2006, including basally divergent lineages with limited evidence for a photosynthetic ancestry (Stiller et al 2014, Dorrell et al 2017, Leonard et al 2018, the monophyly of the ochrophyte members of the stramenopiles strongly suggests that these groups radiated from a plastid-bearing and photosynthetic ancestor, with any non-photosynthetic members within them originating through secondary losses of photosynthesis ( Sev c ıkov a et al 2015, Derelle et al 2016).…”
mentioning
confidence: 99%
“…While it was initially thought that organisms possessing plastids of red versus green algal origins would have exclusively or overwhelmingly genes derived from transfer of endosymbiont genes to their nuclei, this is increasingly recognized as simplistic (Curtis et al, 2012, Dorrell et al, 2017. Since plastid acquisition in euglenoids is a relatively recent event, we sought to investigate the evolutionary origins of the genes derived from gene transfer.…”
Section: ! 10mentioning
confidence: 99%